ADUBAÇÃO NITROGENADA EM COBERTURA NO CULTIVO DO ALGODOEIRO EM SUCESSÃO A BRAQUIÁRIA - QUEIROZ, Ludmila Freitas Marques; ZOZ, Jardel; ZOZ, André; ALIXAME, Danieli; STEINER, Fábio (ANAIS DO ENIC, 2017)
-